The Role of Citizenship Education in the Millennial Generation - Yunita, Sri; Manalu, Magdalena Friskayanti; Putri, Anisa; Silitonga, Miming Kartika Olivia; Sitohang, Sri Rejeky (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the Role of Civic Education for the Millennial Generation. The research method used in this study is a qualitative descriptive type using a comprehensive literature study or library study approach. The results of the study show that Civic Education has a fundamental role in preparing the millennial generation to become intelligent, critical, and actively participating citizens in the digital era. Civic Education also plays a strategic role in developing the civic competence of the millennial generation, such as understanding the constitution and political system, awareness of rights and obligations as citizens. Collaboration between the government, educational institutions, and stakeholders is essential to optimize the strategic role of Civic Education effectively for the millennial generation, so that the millennial generation can face significant challenges in the digital era.